Description of a new species Perissobasis heroni (Hemiptera: Heteroptera: Miridae: Deraeocorinae), found on Coffea arabica, and with a key to Neotropical species of the genus - Ferreira, Paulo Sérgio F.; Uceli, Lorena F.; Coelho, Lívia A.; Pirovani, Victor D. (Zootaxa, 2009)
The newly discovered plant bug Perissobasis heroni is described from specimens collected in Campos Altos city, Minas Gerais State, Brazil, on coffee (Coffea arabica). It was found with a rich arthropod fauna associated with coffee foliage. A diagnosis, description, photographs of the adult male, and selected structures and illustrations of male genitalia are provided to facilitate recognition. A key to species of Perissobasis is also included.